Conformational and processing properties of a high-active ingredient involving soy protein isolates bound with anthocyanins and its application in cake baking - Han Wu; Bin Li; Maria Corradini; Liang Zhong; Jianzhong Zhou; Xiaoli Liu (Food Production, Processing and Nutrition)
Abstract Soybean protein is of plant origin and is commonly appropriate for improving the processing characteristics of foods. This study aimed to explore a novel functional ingredient that contained soybean protein isolate (SPI) and blueberry anthocyanins (BANs). The spatial conformation and secondary structure of SPI-BANs complexes were analyzed using circular dichroism and fluorescence spectroscopy, the processing properties were investigated as well as the retention of antioxidant activity during thermal treatments. Results showed that the contents of free sulfhydryl and free amino groups in complexes increased to 3.50 and 1.19 folds than those of SPI, respectively, while the surface hydrophobicity decreased by 74.23%. Compared with SPI, the BANs-modified SPI had a smaller particle size of 29.12 nm and a lower zeta-potential of -8.73 mV and on the other hand, the complexes possessed higher solubility (83.08%) and foaming and emulsifying properties (115.08% and 54.03 m2/g). After fortification with SPI-BANs, the baking loss rate and adhesiveness of chiffon cake were reduced by 10.82% and improved to 0.24 N.mm, respectively. The high antioxidant activities of SPI-BANs under heat led to the cake’s bioactivities largely enhanced by 1.99 ~ 12.71 folds, being 345.19 µg Trolox/g for the DPPH radical scavenging activity. This study developed the functional food ingredients as antioxidants and a substitute for animal-based proteins in bakery products, which was safe and sustainable by using the dietary components from plant resources. Graphical Abstract